Towards scaleup of graphene production via nonoxidizing liquid exfoliation methods - Stafford,JP; Patapas,A; Uzo,N; Matar,OK; Petit,C (AIChE Journal, 2018)
Graphene, the twodimensional form of carbon, has received a great deal of attention across academia and industry due to its extraordinary electrical, mechanical, thermal, chemical, and optical properties. In view of the potential impact of graphene on numerous and diverse applications in electronics, novel materials, energy, transport, and healthcare, largescale graphene production is a challenge that must be addressed. In the past decade, top–down production has demonstrated high potential for scaleup. This review features the recent progress made in top–down production methods that have been proposed for the manufacturing of graphenebased products. Fabrication methods such as liquidphase mechanical, chemical and electrochemical exfoliation of graphite are outlined, with a particular focus on nonoxidizing routes for graphene production. Analysis of exfoliation mechanisms, solvent considerations, key advantages and issues, and important production characteristics including production rate and yield, where applicable, are outlined. Future challenges and opportunities in graphene production are also highlighted.